2019
DOI: 10.1038/s41598-019-40733-0
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination ecology of Alexandra palm (Archontophoenix alexandrae) and its implication on invasiveness

Abstract: Biological invasions are occurring worldwide, causing enormous economic and ecological damage. Early detection and prediction of invasiveness are the most effective measures to reduce its damage. The Alexandra palm (Archontophoenix alexandrae) is a prolific seeder and an alien species widely planted in tropical China. To help understand the invasion risks posed by this species, lab and field experiments on seed germination were conducted. Results show that the seeds only germinate within a temperature range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The work developed by Loddo et al (2019) that evaluated variability in the invasive species Abutilon theophrasti seed traits demonstrated that achieving a better knowledge of interpopulation variability can allow specific control strategies to be designed, facilitating the development of new management tools. Likewise, germination rates of the Alexandra palm were found to potentially better inform of management strategies for the control of this species (Wen 2019). Considering the obtained results in C. edulis, the differential seed behaviour may determine differential requirements in soil management after eradication.…”
Section: Geographic Intraspecific Variation In Invasive Species: Management Implicationsmentioning
confidence: 84%
“…The work developed by Loddo et al (2019) that evaluated variability in the invasive species Abutilon theophrasti seed traits demonstrated that achieving a better knowledge of interpopulation variability can allow specific control strategies to be designed, facilitating the development of new management tools. Likewise, germination rates of the Alexandra palm were found to potentially better inform of management strategies for the control of this species (Wen 2019). Considering the obtained results in C. edulis, the differential seed behaviour may determine differential requirements in soil management after eradication.…”
Section: Geographic Intraspecific Variation In Invasive Species: Management Implicationsmentioning
confidence: 84%
“…12 The Australian royal palm is an endemic tree in eastern Australia, and the tropical Brazilian climate holds the ideal germination temperature between 20 and 30 °C. This tree specimen can reach up to 25 m in height, producing viable seeds annually, 13 , 14 besides having advantageous disease resistance, and palm heart high quality. 15 Table 1 shows the palm heart Brazilian 2018 production data, according to the Brazilian Institute of Geography and Research (IBGE).…”
Section: Introductionmentioning
confidence: 99%